Multiphysic Two-Phase Flow Lattice Boltzmann: Droplets with Realistic Representation of the Interface (Communications in Computational Physics, 2020)
Free energy lattice Boltzmann methods are well suited for the simulation oftwo phase flow problems. The model for the interface is based on well understoodphysical grounds. In most cases a numerical interface is used instead of the physicalone because of lattice resolution limitations. In this paper we present a frameworkwhere we can both follow the droplet behavior in a coarse scale and solve the interfacein a fine scale simultaneously. We apply the method for the simulation of a dropletusing an interface to diameter size ratio of 1 to 280. In a second simulation, a smalldroplet coalesces with a 42 times larger droplet producing on it only a small capillarywave that propagates and dissipates.